Influence of blue/green versus red and white light sources on human dark adaptation and other selected visual functions - Hendrikse, Egbert Johannes (Rhodes University, Faculty of Science, Department of Human Movement Studies, 1994)
Red interior lighting used to preserve dark-adaptation needs to be replaced in military applications by blue/green lighting which is not detectable by 3rd-generation image intensifiers. This study investigated the influence of blue/green as compared to red and white light of equal photopic intensity on subsequent visual acuity , contrast sensitivity and dark-adaptation. Male subjects (n = 90) were assigned to one of 15 treatment conditions (n = 6) as determined by the colour (blue/green, red or white) and intensity (0.1; 0.4; 1.6; 6.4 and 25.6 cd/mÂ²) of the pre-adaptation stimuli. A modified Goldmann/Weekers adaptometer was used to present the preadaptation stimuli, test stimuli and record visual (luminance) thresholds of each subject. Blue/green lighting had the same affect on visual (photopic) acuity and contrast sensitivity as white and red lighting. Blue/green affected visual (absolute) threshold at the start and during the process of dark-adaptation in the same manner as white but not the same as red lighting. White and red lighting did not differ significantly (p < 0.01) at low intensities (mesopic range) but did at the higher intensities (photopic range). After exposure to blue/green and white light, it will take longer to reach the same level of dark-adaptation than after exposure to red. These time differences increase with" increased intensities. The brightness ratio between red and white lights to produce the same dark-adaptation increases with an increase in intensity. At the upper mesopic region the differences between the effects of white and red lighting on subsequent dark-adaptation become irregular due to the inability to accurately equate non-monochromatic lights in the mesopic range.
Keywords: Light -- Physiological effect; Lighting; Vision -- Research; Night vision; Visual acuity; Color -- Physiological effect; Color vision